尊重教育與課程研究 Respect Education and Curriculum Study - 黃柏叡 Bo-Ruey Huang (Higher Education Foundation, 2024)
尊重教育是近年來國際教育論述的重要理念與倡議，同時也是教育內容與課程 改革的核心要素。本文藉由國際組織中尊重教育的發展析論尊重概念的哲學內涵，試圖討論尊重教育對課程研究的可能意義。本文分為三部分，首先說明國際組織對於尊重教育的相關政策文本，其次析論尊重概念在哲學上的發展方向，最後指出尊重教育對於課程研究的啟示。 Respect education is an important concept and initiative of international education discourse in recent years, and it is also the core element of education content and curriculum reform. This paper attempts to discuss the possible significance of respect education to curriculum study by analyzing the philosophical connotation of respect concept through the development of respect education in international organizations. This paper is divided into three parts. First, it explains the relevant policy texts of international organizations on respect education. Second, it analyzes the philosophical development of the concept of respect. Finally, it points out the enlightenment of respect education for curriculum study.